Pinworms Infection: Review - kafaji, Maani Seher Abid AL-; Alsaadi, Zainab H. (Jour Med Resh and Health Sci, 2022)
Enterobius vermicularis or pinworms is one of intestinal round worm that cause enterobiasis or pinworm infection in humans. the parasite has wide spread than other helminth parasite and has been evaluated to infect about two hundred million individual worldwide annually. Life cycle of parasite is simple and has no intermediate or reservoir hosts ,it consist of three stages ; egg, larvae and adult worm . Egg is the infective stage while the adult worm is pathogenic stage which live in large intestine of host and put their eggs in folded of perianal region of patient .The main symptoms of illness are appendicitis ,itching around the anal region usually at night and nocturnal enuresis ,this symptoms are more common in infected children pinworm infection is related with some factors such as poor of personal hygiene , unsafe human waste disposal and inadequate of safe drinking water. the principal route of transmission is direct contact between infected and healthy human. The method of choice for detection of parasite is observed eggs by exam of stool sample microscopically also visualized of adult worm in stool by naked eye. The best drug against parasite is mebendazole given orally as a single dose.